Energy-saving pad for boiling water and preparation method of energy-saving pad

By preparing and installing the energy-saving pad for boiling water at the bottom of the kettle, the problem of inefficient heat conduction of existing water boiling equipment is solved, and the water boiling efficiency and energy consumption are improved.

CN119685677APending Publication Date: 2025-03-25SHANGHAI SUPERHIGH ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311230111.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The heat conduction mode of existing water boiling equipment is relatively inefficient, resulting in energy waste. How to develop a new water boiling device to improve water boiling efficiency and save energy consumption by improving heat conduction.

Method used

A preparation method for water-burning energy-saving pad is adopted to prepare an energy-saving pad with microporous structure and good thermal conductivity by mixing stainless steel powder, copper powder, nanotitanium oxide, kaolin, diatomaceous earth, carbon nanotubes and syrup, and after stirring, drying, crushing, ultra-fine grinding, screening, tableting, sintering, etc., it is prepared with an energy-saving pad with microporous structure and good thermal conductivity, and is installed at the bottom of the kettle to improve heat conduction.

Benefits of technology

By installing the prepared energy-saving pads on the bottom of the kettle, small bubbles can be quickly generated and jets can be formed, heat transfer efficiency can be improved, water boiling time can be shortened, energy consumption can be saved, and the technical advantages of simple operation, easy to obtain raw materials, and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685677A_ABST
    Figure CN119685677A_ABST
Patent Text Reader

Abstract

The invention discloses an energy-saving pad for boiling water and a preparation method of the energy-saving pad. The method comprises the following steps that stainless steel powder, copper powder, nano titanium oxide, kaolin, kieselguhr, carbon nanotubes and syrup with certain viscosity are weighed according to a certain proportion step to serve as preparation raw materials, the preparation raw materials are put into a stirring machine to be stirred and mixed, and a mixture is generated; the mixed material is dried; the dried mixed material is crushed; carrying out superfine grinding on the crushed mixture; screening out a mixed fine material with the particle size of less than 100 meshes from the mixed material subjected to superfine grinding; performing primary tabletting on the mixed fine material to generate an energy-saving gasket blank; and the energy-saving gasket blank is subjected to sintering, secondary tabletting, deburring and oxide layer removing treatment in sequence, and a finished product is obtained. The energy-saving pad for boiling water, which is rich in microporous structure and has good heat-conducting property, can be prepared, so that the water boiling efficiency is improved, and the water boiling energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of daily necessities, and in particular relates to an energy-saving pad for boiling water, and a preparation method of the energy-saving pad for boiling water. Background Art

[0002] In daily life, people use water boilers, kettles and other equipment to heat and boil tap water to obtain drinking water. Common materials of water boilers include: metal, ceramics, glass, etc.; common shapes of water boilers include: flat bottom, arc bottom, rectangle, sphere, etc. However, no matter what material and shape is sampled, the working form of water heating is similar, mainly relying on layer-by-layer conduction, that is: first, the bottom of the water boiler is heated by an open flame or an electric iron, and the water at the bottom of the water boiler is heated at the first time, and then the water at the bottom heats the water at the middle of the water boiler through heat conduction, and finally the water at the middle heats the water at the high position of the water boiler through heat conduction, until the water at the high position is heated to boil, completing the entire water boiling process. The inventor believes that this is a relatively inefficient heat conduction mode, and part of the energy is wasted in this process. Therefore, how to develop a new type of water boiler that can improve the water boiling efficiency and save water boiling energy by improving heat conduction. It is a research direction that technicians in this field need to carry out. Summary of the invention

[0003] The first purpose of the present invention is to provide a method for preparing an energy-saving pad for water boiling, which can prepare an energy-saving pad for water boiling with a rich microporous structure and good thermal conductivity, so as to improve the water boiling efficiency and save water boiling energy consumption.

[0004] The second object of the present invention is to provide an energy-saving pad for water heating prepared by the above preparation method.

[0005] The first technical solution provided by the present invention is a method for preparing an energy-saving pad for water heating, which comprises the following steps:

[0006] Step 100: 380-400 parts by mass of stainless steel powder, 160-180 parts by mass of copper powder, 60-80 parts by mass of nano titanium oxide, 14-17 parts by mass of kaolin, 4-6 parts by mass of diatomaceous earth, 0.3-1 parts by mass of carbon nanotubes, and 30-40 parts by mass of syrup with a relative viscosity of 2900-3100 mPa·s are weighed respectively as preparation raw materials, and the preparation raw materials are put into a blender and stirred to generate a mixture;

[0007] Step 200: drying the mixed material;

[0008] Step 300: crushing the dried mixed material;

[0009] Step 400: ultra-fine grinding the crushed mixed material;

[0010] Step 500: Screening out mixed fine material with a particle size less than 100 mesh from the ultrafinely ground mixed material;

[0011] Step 600: tableting the mixed fine material to generate energy-saving gasket embryos;

[0012] Step 700: The energy-saving gasket blank is subjected to sintering, secondary pressing, burr removal and oxide layer removal in sequence to obtain an energy-saving gasket for water heating.

[0013] Preferably, the syrup in step 100 comprises: 38%-42% fructose syrup, 52%-55% glucose syrup, 5%-7% oligosaccharide syrup, and the rest is water.

[0014] Preferably, step 200 comprises: placing the mixture into a ceramic dish, placing the dish in an oven and baking the dish at 100° C. for 290-310 minutes.

[0015] Preferably, step 300 comprises: placing the dried mixed material into a hammer crusher for six rounds of hammer crushing, each round lasting 10 minutes.

[0016] Preferably, step 400 comprises: placing the crushed mixed material into a Raymond mill for ultrafine grinding for not less than 60 minutes.

[0017] Preferably, step 500 comprises: placing the ultrafinely ground mixed material into a vibrating screen, and screening out mixed fine material with a particle size less than 100 mesh.

[0018] Preferably, step 600 includes: placing the mixed fine material into a static pressure mold for tableting to generate an energy-saving gasket embryo.

[0019] Preferably, step 700 includes: loading the energy-saving gasket blank into a ceramic mold frame and placing it into a muffle furnace, gradually heating the muffle furnace to 825°C to sinter the energy-saving gasket blank for 600 minutes, taking out the energy-saving gasket blank after sintering, and performing secondary pressing, deburring and oxide layer removal in sequence to obtain an energy-saving gasket for water boiling.

[0020] The second technical solution provided by the present invention is an energy-saving pad for boiling water, which is prepared by any of the preparation methods described above. In practice, the energy-saving pad for boiling water is configured to be installed at the bottom of a heating container such as a kettle.

[0021] Compared with the prior art, the energy-saving pad for boiling water prepared by the preparation method provided by the present invention has excellent thermal conductivity and thermal stability, is safe and reliable, and is suitable for boiling drinking water. The pad surface is distributed with rich microporous structures. When it is arranged at the bottom of the kettle, a large number of fine bubbles can be quickly generated at the microporous structure during the boiling process, and these bubbles can form a jet together during the floating process, thereby quickly transferring the heat from the bottom layer of the kettle to the upper layer of the kettle, shortening the boiling time and saving energy consumption. In addition, the method provided by the present invention also has the technical advantages of simple operation, easy acquisition of raw materials, and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram of the structure of the energy-saving pad for boiling water under a microscope.

[0023] Figure 2 This is a schematic diagram of the working state of the energy-saving pad for boiling water of the present invention when it is placed in a kettle.

[0024] In the figure, the corresponding reference numerals of the components are as follows:

[0025] 100. Energy-saving pad for boiling water; 200. Standard water boiling container. DETAILED DESCRIPTION

[0026] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.

[0027] In the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Features such as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0028] Please refer to Figure 1 .

[0029] Embodiment 1:

[0030] A method for preparing an energy-saving pad 100 for boiling water comprises the following steps:

[0031] Step 100: 380 parts by mass of stainless steel powder, 160 parts by mass of copper powder, 60 parts by mass of nano titanium oxide, 14 parts by mass of kaolin, 4 parts by mass of diatomaceous earth, 0.3 parts by mass of carbon nanotubes, and 30 parts by mass of syrup with a relative viscosity of 2900-3100 mPa·s are weighed as raw materials, and the raw materials are put into a blender for mixing to generate a mixture. The syrup includes: 38% fructose syrup, 55% glucose syrup, 5% oligosaccharide syrup, and the rest is water.

[0032] Step 200: Pour the mixture into a ceramic dish, place it in an oven and bake it at 100° C. for 290 minutes.

[0033] Step 300: placing the dried mixed material into a hammer crusher for six rounds of hammer crushing, each round lasting 10 minutes.

[0034] Step 400: placing the crushed mixed material into a Raymond mill for ultrafine grinding for no less than 60 minutes.

[0035] Step 500 includes: placing the ultrafinely ground mixed material into a vibrating screen, and screening out mixed fine material with a particle size less than 100 mesh.

[0036] Step 600 includes: placing the mixed fine material into a static pressure mold for tableting to form an energy-saving gasket embryo.

[0037] Step 700: Load the energy-saving gasket blank into a ceramic mold frame and place it into a muffle furnace. The muffle furnace is gradually heated (here, the gradient heating specifically refers to heating to 200°C and keeping the temperature constant for 30 minutes, then heating to 400°C and keeping the temperature constant for 30 minutes, then heating to 600°C and keeping the temperature constant for 30 minutes, and finally heating to 825°C. This heating method can effectively prevent the product from cracking and deforming during firing.) to 825°C to sinter the energy-saving gasket blank for 600 minutes. After sintering, take out the energy-saving gasket blank and cool it. Secondary pressing, deburring and oxide layer removal are performed in sequence to obtain the energy-saving pad 100 for water boiling.

[0038] Embodiment 2:

[0039] A method for preparing an energy-saving pad 100 for boiling water comprises the following steps:

[0040] Step 100: 400 parts by mass of stainless steel powder, 180 parts by mass of copper powder, 80 parts by mass of nano titanium oxide, 17 parts by mass of kaolin, 6 parts by mass of diatomaceous earth, 1 part by mass of carbon nanotubes, and 40 parts by mass of syrup with a relative viscosity of 2900-3100 mPa·s are weighed as raw materials, and the raw materials are put into a blender for mixing to generate a mixture. The syrup includes: 42% fructose syrup, 52% glucose syrup, 5% oligosaccharide syrup, and the rest is water.

[0041] Step 200: Pour the mixture into a ceramic dish, place it in an oven and bake it at 100° C. for 310 minutes.

[0042] Step 300: placing the dried mixed material into a hammer crusher for six rounds of hammer crushing, each round lasting 10 minutes.

[0043] Step 400: placing the crushed mixed material into a Raymond mill for ultrafine grinding for no less than 60 minutes.

[0044] Step 500 includes: placing the ultrafinely ground mixed material into a vibrating screen, and screening out mixed fine material with a particle size less than 100 mesh.

[0045] Step 600 includes: placing the mixed fine material into a static pressure mold for tableting to form an energy-saving gasket embryo.

[0046] Step 700: Load the energy-saving gasket blank into a ceramic mold frame and place it into a muffle furnace. The muffle furnace is gradually heated to 825°C to sinter the energy-saving gasket blank for 600 minutes. After sintering, the energy-saving gasket blank is taken out and cooled. Secondary pressing, deburring and oxide layer removal are performed in sequence to obtain an energy-saving pad 100 for water heating.

[0047] Embodiment 3:

[0048] A method for preparing an energy-saving pad 100 for boiling water comprises the following steps:

[0049] Step 100: 390 parts by mass of stainless steel powder, 170 parts by mass of copper powder, 70 parts by mass of nano titanium oxide, 15 parts by mass of kaolin, 5 parts by mass of diatomaceous earth, 0.6 parts by mass of carbon nanotubes, and 35 parts by mass of syrup with a relative viscosity of 2900-3100 mPa·s are weighed as raw materials, and the raw materials are put into a blender for mixing to generate a mixture. The syrup includes: 40% fructose syrup, 52% glucose syrup, 7% oligosaccharide syrup, and the rest is water.

[0050] Step 200: Pour the mixture into a ceramic dish, place it in an oven and bake it at 100° C. for 290-310 minutes.

[0051] Step 300: placing the dried mixed material into a hammer crusher for six rounds of hammer crushing, each round lasting 10 minutes.

[0052] Step 400: placing the crushed mixed material into a Raymond mill for ultrafine grinding for no less than 60 minutes.

[0053] Step 500 includes: placing the ultrafinely ground mixed material into a vibrating screen, and screening out mixed fine material with a particle size less than 100 mesh.

[0054] Step 600 includes: placing the mixed fine material into a static pressure mold for tableting to form an energy-saving gasket embryo.

[0055] Step 700: Load the energy-saving gasket blank into a ceramic mold frame and place it into a muffle furnace. The muffle furnace is gradually heated to 825°C to sinter the energy-saving gasket blank for 600 minutes. After sintering, the energy-saving gasket blank is taken out and cooled. Secondary pressing, deburring and oxide layer removal are performed in sequence to obtain an energy-saving pad 100 for water heating.

[0056] When in use, the energy-saving pad 100 for boiling water prepared in Examples 1-3 is placed on the bottom of a hot water kettle. During the heating process of the hot water kettle, the abundant microporous structure on the surface of the energy-saving pad 100 for boiling water will generate a large number of tiny bubbles that eventually float to the horizontal plane as the water temperature rises. These tiny bubbles have the characteristics of small volume, uniform distribution on the pad surface, and low water resistance. The bubble jet formed together during the floating process can quickly transfer the heat at the bottom of the kettle to the surface water, and form an up-and-down circulation flow in the bubble jet, so that the water in the kettle is evenly heated, the energy utilization rate is improved, and the function of rapid boiling of water is achieved.

[0057] The following comparison experiment of water heating with energy-saving pad 100 is referred to Figure 1-2 :

[0058] A glass kettle with a bottom diameter of 110 mm, a height of 205 mm, a mouth diameter of 80 mm, a capacity of 1500 ml, and 1000 ml of water poured therein is used as the standard water boiling container 200 .

[0059] After 20 rounds of experiments:

[0060] Before the water-boiling energy-saving pad 100 is placed, the average time from starting the heating to boiling the water in the standard water-boiling container 200 is 260 seconds.

[0061] The energy-saving pads 100 for water heating obtained in Examples 1-3 are uniformly configured as circular sheets with a diameter of 80 mm and a bottom thickness of 1 mm (in practice, the shape and thickness of the energy-saving pads 100 for water heating can also be adjusted as required). The energy-saving pads 100 for water heating obtained in Examples 1-3 are respectively placed at the bottom of the above-mentioned standard water heating container 200 and perform water heating operation.

[0062] After 20 rounds of experiments:

[0063] The standard water-boiling container 200 containing the energy-saving pad 100 for water-boiling obtained in Example 1 has an average time of 221 seconds to boil water.

[0064] The standard water-boiling container 200 containing the energy-saving pad 100 for water-boiling obtained in Example 2 takes an average of 223 seconds to boil water.

[0065] The standard water-boiling container 200 containing the energy-saving pad 100 for water-boiling obtained in Example 3 takes an average of 224 seconds to boil water.

[0066] Therefore, after adding the energy-saving pad 100 for water boiling prepared by the present invention, the time taken by the standard water boiling container 200 to boil water is shortened by about 15%.

[0067] The following water boiling experiments were carried out using the pad bodies prepared by adjusting the method of this scheme as comparison examples.

[0068] Comparison Example 1:

[0069] A cushion body is prepared by the following steps:

[0070] Step 100: 400 parts by mass of stainless steel powder, 80 parts by mass of nano titanium oxide, 17 parts by mass of kaolin, 6 parts by mass of diatomaceous earth, and 35 parts by mass of syrup with a relative viscosity of 2900-3100 mPa·s are weighed as raw materials, and the raw materials are put into a blender for mixing to generate a mixture. The syrup includes: 42% fructose syrup, 52% glucose syrup, 5% oligosaccharide syrup, and the rest is water.

[0071] Step 200: Pour the mixture into a ceramic dish, place it in an oven and bake it at 100° C. for 290-310 minutes.

[0072] Step 300: placing the dried mixed material into a hammer crusher for six rounds of hammer crushing, each round lasting 10 minutes.

[0073] Step 400: placing the crushed mixed material into a Raymond mill for ultrafine grinding for no less than 60 minutes.

[0074] Step 500 includes: placing the ultrafinely ground mixed material into a vibrating screen, and screening out mixed fine material with a particle size less than 100 mesh.

[0075] Step 600 includes: placing the mixed fine material into a static pressure mold for tableting to form an energy-saving gasket embryo.

[0076] Step 700: Load the energy-saving gasket blank into a ceramic mold frame and place it into a muffle furnace. The muffle furnace is gradually heated to 825°C to sinter the energy-saving gasket blank for 600 minutes. After sintering, the energy-saving gasket blank is taken out and cooled. Secondary pressing, deburring and oxide layer removal are performed in sequence to obtain a gasket body.

[0077] The pad obtained in Comparative Example 1 was placed at the bottom of the standard water-boiling container 200 to conduct 20 rounds of water-boiling experiments:

[0078] The average time it takes to boil water is 249 seconds. At the same time, according to naked eye observation, the number of bubbles generated on the surface of the pad body is greatly reduced, and the bubble appearance time is delayed by about 10 seconds on average. Therefore, the thermal conductivity and bubble generation rate of the pad body prepared in this comparative example are significantly reduced.

[0079] Comparison Example 2;

[0080] A cushion body is prepared by the following steps:

[0081] Step 100: 390 parts by mass of stainless steel powder, 70 parts by mass of nano titanium oxide, 15 parts by mass of kaolin, 0.6 parts by mass of carbon nanotubes, and 35 parts by mass of syrup with a relative viscosity of 2900-3100 mPa·s are weighed as raw materials, and the raw materials are put into a blender for mixing to generate a mixture. The syrup includes: 40% fructose syrup, 52% glucose syrup, 7% oligosaccharide syrup, and the rest is water.

[0082] Step 200: Pour the mixture into a ceramic dish, place it in an oven and bake it at 100° C. for 290-310 minutes.

[0083] Step 300: placing the dried mixed material into a hammer crusher for six rounds of hammer crushing, each round lasting 10 minutes.

[0084] Step 400: placing the crushed mixed material into a Raymond mill for ultrafine grinding for no less than 60 minutes.

[0085] Step 500 includes: placing the ultrafinely ground mixed material into a vibrating screen, and screening out mixed fine material with a particle size less than 100 mesh.

[0086] Step 600 includes: placing the mixed fine material into a static pressure mold for tableting to form an energy-saving gasket embryo.

[0087] Step 700: Load the energy-saving gasket blank into a ceramic mold frame and place it into a muffle furnace. The muffle furnace is gradually heated to 825°C to sinter the energy-saving gasket blank for 600 minutes. After sintering, the energy-saving gasket blank is taken out and cooled. Secondary pressing, deburring and oxide layer removal are performed in sequence to obtain a gasket body.

[0088] The pad obtained in Comparative Example 2 was placed at the bottom of the standard water-boiling container 200 to conduct 20 rounds of water-boiling experiments:

[0089] The average time it takes to boil water is 239 seconds. At the same time, according to naked eye observation, the number of bubbles generated on the surface of the pad body is greatly reduced, and the bubble appearance time is delayed by about 8 seconds on average. Therefore, the thermal conductivity and bubble generation rate of the pad body prepared in this comparative example are significantly reduced.

[0090] Comparison Example 3:

[0091] A cushion body is prepared by the following steps:

[0092] Step 100: 400 parts by mass of stainless steel powder, 180 parts by mass of copper powder, 80 parts by mass of nano titanium oxide, 17 parts by mass of kaolin, 6 parts by mass of diatomaceous earth, and 35 parts by mass of syrup with a relative viscosity of 2900-3100 mPa·s are weighed as raw materials, and the raw materials are put into a blender for mixing to generate a mixture. The syrup includes: 42% fructose syrup, 52% glucose syrup, 5% oligosaccharide syrup, and the rest is water.

[0093] Step 200: Pour the mixture into a ceramic dish, place it in an oven and bake it at 100° C. for 290-310 minutes.

[0094] Step 300: placing the dried mixed material into a hammer crusher for six rounds of hammer crushing, each round lasting 10 minutes.

[0095] Step 400: placing the crushed mixed material into a Raymond mill for ultrafine grinding for no less than 60 minutes.

[0096] Step 500 includes: placing the ultrafinely ground mixed material into a vibrating screen, and screening out mixed fine material with a particle size less than 100 mesh.

[0097] Step 600 includes: placing the mixed fine material into a static pressure mold for tableting to form an energy-saving gasket embryo.

[0098] Step 700: Load the energy-saving gasket blank into a ceramic mold frame and place it into a muffle furnace. The muffle furnace is gradually heated to 825°C to sinter the energy-saving gasket blank for 600 minutes. After sintering, the energy-saving gasket blank is taken out and cooled. Secondary pressing, deburring and oxide layer removal are performed in sequence to obtain a gasket body.

[0099] The pad obtained in Comparative Example 3 was placed at the bottom of the standard water-boiling container 200 to conduct 20 rounds of water-boiling experiments:

[0100] The average time it takes to boil water is 230 seconds. At the same time, according to naked eye observation, the number of bubbles generated on the surface of the pad body decreases. Therefore, the bubble generation rate of the pad body prepared by the formula of this comparative example is reduced to a certain extent.

[0101] Comparison Example 4:

[0102] A cushion body is prepared by the following steps:

[0103] Step 100: 390 parts by mass of stainless steel powder, 150 parts by mass of aluminum powder, 70 parts by mass of nano titanium oxide, 0.6 parts by mass of carbon nanotubes, 5 parts by mass of diatomaceous earth and 35 parts by mass of syrup with a relative viscosity of 2900-3100 mPa·s are weighed as raw materials, and the raw materials are put into a blender for mixing to generate a mixture. The syrup includes: 40% fructose syrup, 52% glucose syrup, 7% oligosaccharide syrup, and the rest is water.

[0104] Step 200: Pour the mixture into a ceramic dish, place it in an oven and bake it at 100° C. for 290-310 minutes.

[0105] Step 300: placing the dried mixed material into a hammer crusher for six rounds of hammer crushing, each round lasting 10 minutes.

[0106] Step 400: placing the crushed mixed material into a Raymond mill for ultrafine grinding for no less than 60 minutes.

[0107] Step 500 includes: placing the ultrafinely ground mixed material into a vibrating screen, and screening out mixed fine material with a particle size less than 100 mesh.

[0108] Step 600 includes: placing the mixed fine material into a static pressure mold for tableting to form an energy-saving gasket embryo.

[0109] Step 700: Load the energy-saving gasket blank into a ceramic mold frame and place it into a muffle furnace. The muffle furnace is gradually heated to 825°C to sinter the energy-saving gasket blank for 600 minutes. After sintering, the energy-saving gasket blank is taken out and cooled. Secondary pressing, deburring and oxide layer removal are performed in sequence to obtain a gasket body.

[0110] The pad obtained in Comparative Example 4 was placed at the bottom of the standard water-boiling container 200 to conduct 20 rounds of water-boiling experiments:

[0111] The average time it takes to boil water is 209 seconds. The pad body prepared in this comparative example has good thermal conductivity. However, the aluminum ion element in the water after boiling is >0.2mg / L, so this solution cannot meet the drinking water safety standard, is not suitable for boiling drinking water, and has a limited scope of use.

[0112] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Even if various changes are made to the present invention, if these changes fall within the scope of the claims of the present invention and their equivalents, they still fall within the protection scope of the present invention.

Claims

1. A method for preparing an energy-saving pad for water heating, characterized in that: The steps include: Step 100: 380-400 parts by mass of stainless steel powder, 160-180 parts by mass of copper powder, 60-80 parts by mass of nano titanium oxide, 14-17 parts by mass of kaolin, 4-6 parts by mass of diatomaceous earth, 0.3-1 parts by mass of carbon nanotubes, and 30-40 parts by mass of syrup with a relative viscosity of 2900-3100 mPa·s are weighed respectively as preparation raw materials, and the preparation raw materials are put into a blender and stirred to generate a mixture; Step 200: drying the mixed material; Step 300: crushing the dried mixed material; Step 400: ultra-fine grinding the crushed mixed material; Step 500: Screening out mixed fine material with a particle size less than 100 mesh from the ultrafinely ground mixed material; Step 600: tableting the mixed fine material to generate energy-saving gasket embryos; Step 700: The energy-saving gasket blank is subjected to sintering, secondary pressing, burr removal and oxide layer removal in sequence to obtain an energy-saving gasket for water heating.

2. The preparation method according to claim 1, characterized in that: The syrup in step 100 includes: 38%-42% fructose syrup, 52%-55% glucose syrup, 5%-7% oligosaccharide syrup, and the rest is water.

3. The preparation method according to claim 1, characterized in that: Step 200 includes: placing the mixture into a ceramic dish, placing the dish in an oven and baking the dish at 100° C. for 290-310 minutes.

4. The preparation method according to claim 1, characterized in that: Step 300 includes: placing the dried mixed material into a hammer crusher for six rounds of hammer crushing, each round lasting 10 minutes.

5. The preparation method according to claim 1, characterized in that: Step 400 includes: placing the crushed mixed material into a Raymond mill for ultrafine grinding for no less than 60 minutes.

6. The preparation method according to claim 1, characterized in that: Step 500 includes: placing the ultrafinely ground mixed material into a vibrating screen, and screening out mixed fine material with a particle size less than 100 mesh.

7. The preparation method according to claim 1, characterized in that: Step 600 includes: placing the mixed fine material into a static pressure mold for tableting to form an energy-saving gasket embryo.

8. The preparation method according to claim 1, characterized in that: Step 700 includes: loading the energy-saving gasket blank into a ceramic mold frame and placing it into a muffle furnace, gradually increasing the temperature of the muffle furnace to 825°C to sinter the energy-saving gasket blank for 600 minutes, taking out the energy-saving gasket blank after sintering, and performing secondary pressing, deburring and oxide layer removal in sequence to obtain an energy-saving gasket for water heating.

9. An energy-saving pad for boiling water, characterized in that: The method is prepared according to any one of claims 1 to 8.